(untitled) (Research, Society and Development, 2020)
The consumption of baby food for children’s line grows over the years and has gained more and more prominence in the Brazilian market due to its great practicality. In parallel, there is a significant increase in the excessive intake of sodium and potassium by consumers, also due to the high intake of industrialized products. Thus, this work aimed to quantify the sodium and potassium content in baby food, using the method of flame photometry, in twenty-seven samples of baby food from three different brands marketed in the city of Chapecó / SC. For research, industrialized baby food and organic baby food were used. The results were subjected to analysis of variance (ANOVA) and then to the Tukey means comparison test at a significance level of 5% (p <0.05). For sodium, all samples, regardless of their origin, exceeded the values described on the label and their daily intake of 1500 mg / day. Organic meat-based porridge 8 was the one with the highest value, 12.262 mg sodium / g of the sample. For potassium, all samples exceeded the daily intake value, 3.5 mg / day. This highlights the importance of implementing and maintaining food monitoring programs in the country, as well as providing tools to assist industries in controlling the addition of salt to their diets.